Chinese International Students’ Experiences in American Higher Education Institutes: A Critical Review of the Literature - Zhang-Wu, Qianqian (Journal of International Students, 2018)
Using database searches in ProQuest Sociology, Education Research Complete, ERIC, and Google Scholar, this landscape literature review provides research synthesis and analysis on research designs, underlying assumptions and findings of 21 recent peer-reviewed scholarly articles focusing on Chinese international students’ experiences in American higher education institutes. Patterns observed across studies regarding colorblind racism are presented in the discussion. Towards the end, this review closes with implications and directions for future research.